Preliminary Phytochemical and Antimycobacterial Investigation of Some Selected Medicinal Plants of Endau Rompin, Johor, Malaysia - Sanusi, Shuaibu Babaji; Abu Bakar, Mohd Fadzelly; Mohamed, Maryati; Sabran, Siti Fatimah (Journal of Science and Technology, 2018)
Tuberculosis (TB), the primary cause of morbidity and mortality globally is a great public health challenge especially in developing countries of Africa and Asia. Existing TB treatment involves multiple therapies and requires long duration leading to poor patient compliance. The local people of Kampung Peta, Endau Rompin claimed that local preparations of some plants are used in a TB symptoms treatment. Hence, there is need to validate the claim scientifically.  Thus, the present study was designed to investigate the in vitro anti-mycobacterial properties and to screen the phytochemicals present in the extracts qualitatively. The medicinal plants were extracted using decoction and successive maceration. The disc diffusion assay was used to evaluate the anti-mycobacterial activity, and the extracts were subjected to qualitative phytochemical screening using standard chemical tests. The findings revealed that at 100 mg/ml concentration, the methanol extract of Nepenthes ampularia displayed largest inhibition zone (DIZ=18.67 ± 0.58), followed by ethyl acetate extract of N. ampularia (17.67 ± 1.15) and ethyl acetate extract of Musa gracilis (17.00 ± 1.00). The phytochemical investigation of these extracts showed the existence of tannins, flavonoids, alkaloids, terpenoids, saponins, and steroids. The pronounced anti-mycobacterial properties displayed by the screened medicinal plants scientifically proved the claim by traditional people of Endau Rompin Johor. It is suggested that the extracts may be considered for further evaluation.